Pengaruh Kepercayaan Merek Dan Citra Merek Terhadap Minat Beli Ulang “Kopi Toraja” Di Coffee Josh Situbondo - Randika Fandiyanto; Ratih Endriyasari Kurniawan (Fakultas Ekonomi Universitas Panca Marga, 2019)
This study aims to determine the effect of brand trust and brand image on interest in repurchasing “Toraja coffee” in coffee josh Situbondo. This research uses a descriptive method. The population in this study were all coffee consumers who consumed Toraja coffee as many as 90 respondents. Data collection is done by observation, interview, and questionnaires. The data obtained were analyzed using statistical formulas, namely by using multiple linear regression analysis, t test, F test and determination coefficient which the processing was carried out with the SPSS version 22 program windows 7. The results of multiple linear regression indicate that Y = 1,295E-16 + 0,249X1 + 0,376X2 + e. t-test results show that all independent variables (brand trust and brand image) have a positive influence on dependent variable namely (repurchase interest). F test results show that the research hypothesis which states that brand trust variables and brand image simultaneously have a significant effect on repurchase interest can be accepted. Based on the dominant result the brand image variables has a dominant influence on repurchase interest with a variable value that is greater than the Brandt trust variable. The determination coefficient obtained is 0,269. This means that 26,9% repurchase interest is influenced by brand trust variables and brand image, the remaining 73,1% is influenced by other variables. Keywords: Brand Trust and Brand Image, Repurchase Interest